Impacts of the COVID-19 Pandemic on the CODE ST-Segment Elevation Myocardial Infarction Program: A Quantitative and Qualitative Analysis - Eka Ginanjar; Arif Mansjoer; Lusiani Rusdi; Rizky Ramadantie; Hadiki Habib; Lies Dina Liastuti; Sally Aman Nasution; Idrus Alwi; Abdul Rashid (Interna Publishing, 2024)
Background: The code ST-segment elevation myocardial infarction (STEMI) program is an operational standard of integrated service for STEMI patients carried out by Dr. Cipto Mangunkusumo Hospital. The emerging coronavirus disease 2019 (COVID-19) outbreak brought about many changes in the management of healthcare services, including the code STEMI program. This study aimed to evaluate the healthcare service quality of the Code STEMI program during the COVID-19 pandemic based on the Donabedian concept.  Methods: This was a mixed-methods study using quantitative and qualitative analyses. It was conducted at the Dr. Cipto Mangunkusumo Hospital, a national referral hospital in Indonesia. We compared the data of each patient, including response time, clinical outcomes, length of stay, and cost, from two years between 2018-2020 and 2020-2022 as the pre-COVID-19 code STEMI and COVID-19 Code STEMI periods, respectively. Interviews were conducted to determine the quality of services from the perspectives of stakeholders. Results: A total of 195 patients participated in the study: 120 patients in pre-COVID-19 code STEMI and 75 patients in COVID-19 code STEMI. Our results showed that there was a significant increase in patient's length of stay during the COVID-19 pandemic (4 days vs. 6 days, p < 0.001). Meanwhile, MACE (13% vs. 11%, p = 0.581), the in-hospital mortality rate (8% vs. 5%, p = 0.706), door-to-wire crossing time (161 min vs. 173 min, p = 0.065), door-to-needle time (151 min vs. 143 min p = 0.953), and hospitalization cost (3,490 USD vs. 3,700 USD, p = 0.945) showed no significant changes. In terms of patient satisfaction, patients found code STEMI during COVID-19 to be responsive and excellent. Conclusion: The implementation of the code STEMI program during the COVID-19 pandemic revealed that modified pathways were required because of the COVID-19 screening process. According to the Donabedian model, during the pandemic, the code STEMI program's healthcare service quality decreased because of a reduction in efficacy, effectiveness, efficiency, and optimality. Despite these limitations attributed to the pandemic, the code STEMI program was able to provide good services for STEMI patients.